Anti-malarial activity of 6-(8'Z-pentadecenyl)-salicylic acid from Viola websteri in mice - Park Won-Hwan; Kang Eun-Young; Seo Su-Hyun; Chung Ill-Min; Moon Hyung-In (Malaria Journal, 2009)
Abstract Background Petroleum ether extracts of Viola websteri Hemsl (Violaceae) were reported to have anti-plasmodial activity against Plasmodium falciparum in vitro, with this activity being largely attributable to 6-(8'Z-pentadecenyl)-salicylic acid (6-SA). Methods The schizontocidal activity of 6-SA on early Plasmodium berghei infections was evaluated in a four-day test. The possible 'repository' activity of 6-SA was assessed using the method described by Peters. The median lethal dose (LD50) of 6-SA, when given intraperitoneally, was also determined using uninfected ICR mice and the method of Lorke. Results In the present study, 6-SA was found to have anti-malarial activity in vivo, when tested against P. berghei in mice. 6-SA at 5, 10 and 25 mg/kg·day exhibited a significant blood schizontocidal activity in four-day early infections, repository evaluations and established infections with a significant mean survival time comparable to that of the standard drug, chloroquine (5 mg/kg·day). Conclusion 6-SA possesses a moderate anti-malarial activity that could be exploited for malaria therapy.